+0

+3
59
2

https://web2.0calc.com/questions/help_48150

Apr 10, 2020

#1
+5

Let p  be  the larger  positive  integer  and q  be the smaller

p + q  =  pq

Square this

p^2 + 2pq + q^2  = p^2q^2

p^2 + q^2 =  p^2q^2 - 2pq       (1)

And

p - q  =  7

Square this  and we get that

p^2 - 2pq + q^2  =  49

p^2 + q^2  =  49 + 2pq       (2)

(1) and (2)   imply  that

p^2q^2 - 2pq  =  49 + 2pq

p^2q^2 - 4pq  = 49

Let  pq  = x

x^2  - 4x  =  49       complete the square on x

x^2 - 4x + 4  =  49 + 4

(x - 2)^2  = 53       take  both roots

x - 2  = √53           or        x - 2  =  -√53

x =  2 + √53                       x = 2 - √53

pq  = 2 + √53                     pq = 2 - √53

We can  simplify  the  given fraction as

p^2 q^2                  (pq)^2

__________   =   _________

p^2 + q^2               p^2  + q^2

We  have two  cases

pq  = 2 + √53

(pq)^2  =  4 + 4√53 + 53 =  57 + 4√53

And p^2 + q^2   =  49 + 2(pq)   =  49 + 2(2 + √53)  = 53 + 2√53

So

(pq)^2                         57  + 4√53     [ 53 - 2√53]           2597 + 98√53

_________   =         ___________  ___________ =  ______________

p^2 + q^2                   53  + 2√53      [53 - 2√53]               2597

And

a = 2597, b = 98 , c  = 53  and d = 2597     and their sum =  5345

Also

pq =  2 - √53

(pq)^2  = 4 - 4√53 + 53  =   57 - 4√53

And p^2 + q^2  =   49 + 2(pq)  =  49 + 2(2 - √53)  =    53 - 2√53

So

)pq)^2                  57  - 4√53       [ 53 + 2√53 ]         2597  - 98√53

________   =   ___________   ____________ =   _____________

p^2 + q^2            53  - 2√53       [ 53  + 2√53]             2597

And

a = 2597 , b = -98 , c = 53 , d  = 2597    and their sum = 5149   Apr 10, 2020
#2
+2

Thank you!

Apr 10, 2020